International Transactions in National Income Accounts - Salant, Walter S. (The Review of Economics and Statistics, 1951)
INC,CE the war there has been a constantly wider use of national income and product accounts as a framework for discussions of economic policy. standard treatment of international transactions in these accounts has confused many laymen, while its further development in the tables on The Nation's Economic Budget, which appeared first in the President's Economic Report itself (and now appear in the accompanying ElConomic Review by the Council of Economic Advisers), is even less clear. Beyond this, the foreign investment component of the gross national product presents a puzzling problem to those who wish to adjust the components of the national expenditure series for price changes or to make seasonal adjustments in the quarterly data. This article attempts to deal with some of the questions raised by the present treatment and to offer some positive suggestions, in the hope of stimulating further discussion. third part of the article attempts to explain how the concepts of receipts, expenditures, and particularly the net item excess of receipts or expenditures shown in The Nation's Economic Budget tables for the different sectors of the economy have actually been applied to international transactions.